Managingtomato bacterial wilt by suppressing Ralstonia solanacearum population in soil and enhancing host resistance through fungus-derived furoic acid compound - Meijin Ye; Hong Feng; Jianghong Hu; Qing Yu; Songqing Liu (Frontiers in Plant Science, 2022)
Synthetic chemical pesticides are primarily used to manage plant pests and diseases, but their widespread and unregulated use has resulted in major health and environmental hazards. Using biocontrol microbes and their bioactive compounds is a safe and sustainable approach in plant protection. In this study, a furoic acid (FA) compound having strong antibacterial activity against soil-borne phytopathogenic bacterium Ralstonia solanacearum [causal agent of bacterial wilt (BW) disease] was isolated from Aspergillus niger and identified as 5-(hydroxymethyl)-2-furoic acid compound through spectroscopic analyses (liquid chromatography–mass spectrometry (MS), electron ionization MS, and NMR). The SEM study of bacterial cells indicated the severe morphological destructions by the FA compound. The FA was further evaluated to check its potential in enhancing host resistance and managing tomato BW disease in a greenhouse experiment and field tests. The results showed that FA significantly enhanced the expression of resistance-related genes (PAL, LOX, PR1, and PR2) in tomato and caused a significant reduction (11.2 log10 colony-forming units/g) of the R. solanacearum population in soil, resulting in the reduction of bacterial wilt disease severity on tomato plants and increase in plant length (58 ± 2.7 cm), plant biomass (28 ± 1.7 g), and root length (13 ± 1.2 cm). The findings of this study suggested that the fungus-derived FA compound can be a potential natural compound of biological source for the soil-borne BW disease in tomato.